Teks Ucapan Yang Hormat Profesor Dato’ Dr. Daing Nasir Ibrahim Naib Canselor Universiti Malaysia Pahang Sempena Opening Ceremony of Innovate Malaysia Design Conference 2016 - Pejabat, Naib Canselor UMP (Universiti Malaysia Pahang, 2016)
Since the conference is concurrently organized with Innovate Malaysia Design Competition 2016, I am glad that both events have received strong support from our committed and credible partners namely TalentCorp, Altera, Intel, Keysight Technologies, Mathworks, Microsoft, Motorola Solutions, National Instruments, Silterra, Vitrox, Daikin, Sime Darby, Telekom Malaysia and Wildlife Conservation Society Malaysia.